Emerging Role of Translational Digital Biomarkers Within Home Cage Monitoring Technologies in Preclinical Drug Discovery and Development - Baran, Szczepan W.; Bratcher, Natalie; Dennis, John; Gaburro, Stefano; Karlsson, Eleanor M.; Maguire, Sean; Makidon, Paul; Noldus, Lucas P. J. J.; Potier, Yohann; Rosati, Giorgio; Ruiter, Matt; Schaevitz, Laura; et al. (Frontiers in Behavioral Neuroscience, 2022)
In drug discovery and development, traditional assessment of human patients and preclinical subjects occurs at limited time points in potentially stressful surroundings (i.e., the clinic or a test arena) which can impact data quality and welfare. However, recent advances in remote digital monitoring technologies enables assessment of human patients and preclinical subjects across multiple time points in familiar surroundings. The ability to monitor a patient throughout disease progression, provides an opportunity for more relevant and efficient diagnosis as well as improved assessment of drug efficacy and safety. In preclinical in vivo animal models, these digital technologies allow for continuous, longitudinal, and non-invasive monitoring in the home environment. This manuscript provides an overview of digital monitoring technologies including their history and evolution, current engagement through use cases, and impact of digital biomarkers on drug discovery and the 3Rs. We also discuss barriers to implementation and strategies to overcome them. Finally, we address data consistency and technology standards from the perspective of technology providers, end-users, and subject matter experts. Overall, this review establishes an improved understanding of the value and implementation of digital biomarker technologies in preclinical research.